Single Oral Dose Pharmacokinetics of Decursin, Decursinol Angelate, and Decursinol in Rats - Li, Li; Zhang, Jinhui; Xing, Chengguo; Kim, Sung-Hoon; Lü, Junxuan (Planta Medica, 2013)
Decursin and decursinol angelate are the major components in the alcoholic extract of the root of Angelica gigas Nakai. Our previous work convincingly demonstrated that both decursin and decursinol angelate were rapidly converted to decursinol in mice after administration by either oral gavage or i. p. injection. In the current study, we compared for the first time the plasma profiles of decursinol, when equal moles of decursin/decursinol angelate or decursinol were given to rats by oral gavage, and investigated the effect of different formulas and other chemicals in Angelica gigas extract on the bioavailability of decursinol. Our results show that gavage of decursinol led to a faster attainment of plasma decursinol peak (Tmax ~ 0.7 h) and much higher peak levels than an equal molar amount administered as decursin/decursinol angelate mixture or as Angelica gigas ethanol extract, resulting in 2–3 fold higher bioavailability as estimated by the area under the curve of the respective regimens (65 012 vs. 27 033 h · ng/mL for decursinol and decursin/decursinol angelate treatment groups, respectively). Compared to a formula based on ethanol-PEG400-Tween80, carboxyl methyl cellulose was a less optimized vehicle. In addition, we detected peak levels of decursin and decursinol angelate in the plasma of rats administered with decursin/decursinol angelate or Angelica gigas extract in the nM range (Tmax ~ 0.5 h) with a newly established sensitive UHPLC-MS/MS method. Furthermore, our data support the liver, instead of intestine, as a major organ site where decursin and decursinol angelate were hydrolyzed to decursinol with a S9 microsomal in vitro metabolism assay. Taken together, our study provided important PK, LC-MS/MS methodology, formulation and metabolism insights in a rodent model for the rational design of in vivo efficacy studies of the corresponding chemicals in the future.
Keywords: decursin; decursinol angelate; decursinol; Angelica gigas; Apiaceae; LC-MS/MS